Biological and pharmacological roles of pyroptosis in pulmonary inflammation and fibrosis: recent advances and future directions - Ya Liu; Danxia Wang; Xiang Liu; Haibin Yuan; Dan Liu; Yixiang Hu; Shipeng Ning (Cell Communication and Signaling)
Abstract Pyroptosis, an inflammatory regulated cell death (RCD) mechanism, is characterized by cellular swelling, membrane rupture, and subsequent discharge of cellular contents, exerting robust proinflammatory effects. Recent studies have significantly advanced our understanding of pyroptosis, revealing that it can be triggered through inflammasome- and caspase-independent pathways, and interacts intricately with other RCD pathways (e.g., pyroptosis, necroptosis, ferroptosis, and cuproptosis). The pathogenesis of pulmonary fibrosis (PF), including idiopathic pulmonary fibrosis (IPF) and other interstitial lung diseases, involves a multifaceted interplay of factors such as pathogen infections, environmental pollutants, genetic variations, and immune dysfunction. This chronic and progressive interstitial lung disease is characterized by persistent inflammation, extracellular matrix (ECM) accumulation, and fibrotic alveolar wall thickening, which potentially contribute to deteriorated lung function. Despite recent advances in understanding pyroptosis, the mechanisms by which it regulates PF are not entirely elucidated, and effective strategies to improve clinical outcomes remain unclear. This review strives to deliver a comprehensive overview of the biological functions and molecular mechanisms of pyroptosis, exploring its roles in the pathogenesis of PF. Furthermore, it examines potential biomarkers and therapeutic agents for anti-fibrotic treatments.